Total cerebral blood volume changes drive macroscopic cerebrospinal fluid flux in humans - Zimmermann, Juliana; Boudriot, Clara; Eipert, Christiane; Hoffmann, Gabriel; Nuttall, Rachel; Neumaier, Viktor; Bonhoeffer, Moritz; Schneider, Sebastian; Schmitzer, Lena; Kufer, Jan; Kaczmarz, Stephan; Hedderich, Dennis M.; et al. (PLoS biology, 2025)
In the mammalian brain, the directed motion of cerebrospinal fluid (CSF-flux) is instrumental in the distribution and removal of solutes. Changes in total cerebral blood volume (CBV) have been hypothesized to drive CSF-flux. We tested this hypothesis in two multimodal brain imaging experiments in healthy humans, in which we drove large changes in total CBV by neuronal burst-suppression under anesthesia or by transient global vasodilation in a hypercapnic challenge. We indirectly monitored CBV changes with a high temporal resolution based on associated changes in total brain volume by functional MRI (fMRI) and measured cerebral blood flow by arterial spin-labeling. Relating CBV-sensitive signals to fMRI-derived measures of macroscopic CSF flow across the basal cisternae, we demonstrate that increasing total CBV extrudes CSF from the skull and decreasing CBV allows its influx. Moreover, CSF largely stagnates when CBV is stable. Together, our results establish the direct coupling between total CBV changes and CSF-flux.
Gesehen am 03.12.2025